The Qur’ānic View of History, Revelation, and Prophethood: An Exercise in Comparative Theology - Avcı, Betül (Journal of ecumenical studies, 2021)
This essay examines the qur’ānic view of revelation and prophethood in relation to the biblical and early Christian theologies of revelation. It argues that Christian theology of revelation, inspired by the Bible and early church Fathers, has a progressivist nature. Accordingly, while Christian revelation culminates in the Incarnation, the preceding period stands as a preparation. However, the qur’ānic account of revelation and prophethood suggests neither a gradual development awaiting the Prophet Muhammad nor a preceding preparation for him. This is because Allah is Merciful and Just and has always been equally accessible to all humanity. In the end, while the Prophet Muhammad is the final select individual as a prophet who conveyed the communication between God and the creation, Islam is the final account of this communication and the system of right conduct. Such finality suggests neither fulfillment nor culmination as believed in Christianity.